Relevansi Kesejahteraan Ekonomi Keluarga dengan Peningkatan Perceraian di Kabupaten Bone - Sitti Nikmah Marzuki (Al-Risalah: Jurnal Hukum Keluarga Islam (Ahwal Al-Syakhsiyah), 2021)
AbstractThe are many cases of adults who ended his life due to economic pressures. Even family life usually becomes quiet when the husband is not able to meet its obligations to provide for the family, cause prolonged conflict that will end in divorce. The divorce rate in Bone regency is very high, not least the economic factors. This situation triggered conflict in the family. The problem then arises is the welfare of the family, if husbend cannot perform its responsibility to make a living. The wife is not able to help her husband to earn a living. But if it isconstantly in progress, and the wife feels particularly a dual role then this problem can be more pointed and lead to conflict within the household and encourage the wife nor the husband decided to divorce. Therefore, the welfare of the family have relevance to the large number of divorces in Bone regency with reasons to leave for economic reasons.